ANALISI KOMPETENSI PENDIDIK DALAM TAFSIR AL MISHBAH Q.S. AL MUJADILAH AYAT 11 - muhammadiqbalhafiz (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
The many problems that occur in the world of education which result in not achieving educational goals are something that must be considered so that it is reviewed how problems in the world of education can be overcome. One factor that is the center of attention is the quality of the educators. This study aims to explain how the competence of educators contained in surah Al Mujadilah verse 11 is based on the explanation from the Al Misbah interpretation book with the aim that educators will be able to have competence in carrying out their duties as educators. In this study, researchers used qualitative methods, in which researchers presented discussions in journals by providing explanations from various literature. The type of research chosen is the library research method. The results of this study explain the four educator competencies that must be possessed by every educator when carrying out their profession based on the perspective of the Qur'an. These competencies are considered important in advancing the world of education to create a generation that has a high intellect and good character. Because the good side of students will emerge through the education provided by educators. An educator is a role model for his students, therefore to achieve the goals of learning starts from preparing himself as an educator who has competence in imparting knowledge to his students.